Diversity in mitotic DNA repair efficiencies between commercial inbred maize lines and native Central American purple landraces - Carlos Víquez-Zamora; Sergio Castro-Pacheco; María Viñas; Pablo Bolaños-Villegas (CABI Agriculture and Bioscience)
Abstract Background Homologous recombination allows plants to repair double strand breaks in DNA, which if unrepaired may lead to cell death. In this project, we determined the relative DNA repair efficiency of the US inbred lines B73 and Mo17 and Central American purple landraces from Guatemala and Costa Rica with the purpose to uncover genetic differences that may allow for the breeding of new lines better adapted to tolerate DNA damage caused by environmental factors. Methods Single cell electrophoresis was used to analyze the relative DNA repair ability of several lines from the US and Central America exposed to radiomimetic agent Zeocin, and these results were in turn compared with High Resolution Melting analyses of key genes for homologous DNA recombination. The significance of differences between treatments was evaluated with the Di Rienzo, Guzmán and Casanoves (DGC) test, while High Resolution Melting and difference curves were generated with the R package “HRM.curve”. Curves were created as a negative first derivative (−d(RFU)/d(T)) using normalized relative fluorescence values (RFUs) after background removal. The kinase gene ZeaATM1 was amplified and sequenced in B73, Mo17, P1 and P2. Multiple sequence alignment of DNA and aminoacid sequences was performed using ClustalW. Protein sequence analysis was done in UniProt to compare the resulting aminoacid sequences from maize to the available sequences from Arabidopsis thaliana ecotype Col-0 (ATM protein code: Q9M3G7). Results Single-cell electrophoresis results of statistical significance suggested that the landrace P1-Pujagua Santa Cruz is resistant to damage caused by the radiomimetic agent Zeocin, and landrace P2-Pujagua La Cruz was able to repair all DNA damage after 24 h of treatment and 1 h of recovery time. In contrast, line Mo17 was unable to repair the damage, but B73 and the landraces Jocopilas (Guatemalan), Orotina Congo, and Talamanca were partially able to repair the DNA damage. High resolution melting analysis of the putative homologous DNA repair gene ZeaATM1 revealed that landraces P1 and P2 may harbor polymorphisms for this gene, and P1 may harbor other polymorphisms for the transcription factor ZeaSOG1 as well as the tumor suppressor ZeaRAD51 and recombinase ZeaBRCA1. The kinase gene ZeaATM1 was sequenced, and results indicate that in lines P1 and P2 there are polymorphisms near and within the FATC domain, a domain required for the activation of ATM1-mediated repair of DNA damage. Conclusions Significant differences in DNA repair efficiency exist between inbred lines and landraces of maize and may be linked to allelic diversity in key genes for homologous recombination. Thus, Central American landraces could be used for breeding tolerance to genotoxic stress.